"Invincibles" and "invisibles": CEO status and the 'Matthew effect' in strategic decision-making. Issue 3 (June 2020) - Fralich, Russell; Bitektine, Alex
Abstract: A failure of a large corporate investment project launched by a CEO may affect not only CEO's bonus and equity holdings, but also personal status and future career prospects. Yet, Merton's (1968) "Matthew Effect" would suggest that the risks and benefits associated with risky investment projects may be different for CEOs of different status. High-status CEOs are better able to decouple their status from their firm's performance failure and are in a better position to claim credit for the firm's successes. On the other hand, given that third parties have greater reluctance to accept quality claims of low-status actors, lower status CEOs might not receive a commensurate credit for the success of a project, but might be exposed to a disproportionate amount of blame in case of project failure. Since actors are usually aware of the presence of the Matthew Effect in their field, we can expect that the differential outcomes produced by it will be factored into actors' expected utility calculations, affecting CEOs' attitudes to risk and visibility of their investment prospects. The findings from a 19-year sample of U.S.-based cellular telephone operators provide support for the theorized relationship between the Matthew Effect and CEOs' investment choices.